Psychology-Pedagogical Conditions of the Formation of Spiritual-Moral Self-Actualization of a Person - I V Yezhov (Peoples' Friendship University of Russia (RUDN University), 2008)
Psychological and pedagogical principles, methods and conditions of the development of spiritual-moral self-actualization of a person from a conventional stage in secular or religious-dogmatic forms to a post-conventional stage - the religious-humanistic form of spiritual-moral self-actualization of a person are considered in the article. The results of long-comparative researches of the features and general laws of the formation of spiritual-moral self-actualization of the personality of students in the framework of comprehensive education and in the innovative pedagogical system including the subjects aimed at developing spiritual-moral personality of the rising generation are submitted.